Fusion imaging of contrast-enhanced ultrasound and contrast-enhanced CT or MRI before radiofrequency ablation for liver cancers - Bo, Xiao-Wan (Br J Radiol, 2016)
OBJECTIVE: To investigate the usefulness of fusion imaging of contrast-enhanced ultrasound (CEUS) and CECT/CEMRI before percutaneous ultrasound-guided radiofrequency ablation (RFA) for liver cancers. METHODS: 45 consecutive patients with 70 liver lesions were included between March 2013 and October 2015, and all the lesions were identified on CEMRI/CECT prior to inclusion in the study. Planning ultrasound for percutaneous RFA was performed using conventional ultrasound, ultrasound-CECT/CEMRI and CEUS and CECT/CEMRI fusion imaging during the same session. The numbers of the conspicuous lesions on ultrasound and fusion imaging were recorded. RFA was performed according to the results of fusion imaging. Complete response (CR) rate was calculated and the complications were recorded. RESULTS: On conventional ultrasound, 25 (35.7%) of the 70 lesions were conspicuous, whereas 45 (64.3%) were inconspicuous. Ultrasound-CECT/CEMRI fusion imaging detected additional 24 lesions thus increased the number of the conspicuous lesions to 49 (70.0%) (70.0% vs 35.7%; p < 0.001 in comparison with conventional ultrasound). With the use of CEUS and CECT/CEMRI fusion imaging, the number of the conspicuous lesions further increased to 67 (95.7%, 67/70) (95.7% vs 70.0%, 95.7% vs 35.7%; both p < 0.001 in comparison with ultrasound and ultrasound-CECT/CEMRI fusion imaging, respectively). With the assistance of CEUS and CECT/CEMRI fusion imaging, the confidence level of the operator for performing RFA improved significantly with regard to visualization of the target lesions (p = 0.001). The CR rate for RFA was 97.0% (64/66) in accordance to the CECT/CEMRI results 1 month later. No procedure-related deaths and major complications occurred during and after RFA. CONCLUSION: Fusion of CEUS and CECT/CEMRI improves the visualization of those inconspicuous lesions on conventional ultrasound. It also facilitates improvement in the RFA operators' confidence and CR of RFA. ADVANCES IN KNOWLEDGE: CEUS and CECT/CEMRI fusion imaging is better than both conventional ultrasound and ultrasound-CECT/CEMRI fusion imaging for lesion visualization and improves the operator confidence, thus it should be recommended to be used as a routine in ultrasound-guided percutaneous RFA procedures for liver cancer.